Dynamic performance requirements for permanent grandstands subject to crowd action : recommendations for management, design and assessment (Institution of Structural Engineers, 2008)
This report supersedes both Dynamic Performance Requirements for permanent grandstands subject to crowd action; Interim guidance on assessment and design (2001) and Dynamic testing of Grandstands and seating decks (2002). Written for everyone who has responsibility for grandstands, including owners, operators, managers, architects, insurers and engineering designers, as well as local authority staff dealing with building control and safety issues. -- Provided by publisher.
Keywords: Grandstands -- Design and construction.; Concrete construction -- Testing.; Structural dynamics.; elektronické knihy; electronic books